ANALYSIS OF ROLE CONFLICT AND ROLE AMBIGUITY TOWARDS CYBERLOAFING AT PT. BANK SULUTGO MANADO - Lonteng, Ekaristi; Kindangen, Paulus; Tumewu, Ferdinand J. (FEB Universitas Sam Ratulangi Manado, 2019)
Abstract: Along with the increasingly competitive business competition, companies are required to perform better. The company demands employees to play a role in all positions. But this is contrary to the ability and expertise of limited employees which can lead to role ambiguity and role conflict which these roles are part of work stressors. Work stressors are triggers of stress and to avoid stress, employees conduct cyberloafing. This research aims to analyze the influence of role conflict and role ambiguity towards cyberloafing at PT. Bank SulutGo Main Branch Office Manado. This research used the quantitative method with questionnaires used to collect the data, Multiple Linear Regression as the tool of analysis and 55 employees as the sample. The result shows that role conflict has a positive but no significant influence on cyberloafing, while role ambiguity has a positive and significant influence on cyberloafing. Based on the result, it is recommended for the company to be more clear about the job description of each employee so that they understand the authority, roles, and responsibilities within the company, be even more assertive in imposing rules on the use of the internet in the workplace so that employees avoid cyberloafing.Â Keywords: role conflict, role ambiguity, cyberloafing.